An Assessment of the government information campaign on the 1998 party-list election - Laylo, Annaliza V.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This thesis entitled An Assessment of the Government Information Campaign on the 1998 Party-List Election is an evaluation study of the information campaign on the 1998 Party-List election. Its main objective is to determine whether the information campaign was able to reach its objectives. It also calls comments from the key stakeholders in the 1998 Party-List election. It examines the different stages and elements of the information campaign. It also seeks to determine the factors that affected the outcome of the information campaign. Several research materials were reviewed to aid the analysis in this study. In general, the studies reviewed explain the interaction or interrelation of the different elements of the communication process. The framework used in this study is based on the Directive Theory of the Persuasion Process developed by William J. McGuire, which illustrates the persuasion matrix which involves the input and the output variables. Data gathering was conducted using the focused interview method. Key stakeholders in the Party-List election were interviewed. An inventory of the campaign materials was also made. Interview guide and inventory guide constructed to gather data. Data gathering process took four months. The main variables in this study are the stages of communication campaign process and the different elements of the communication process. Based on the analysis of the responses of the key stakeholders and the analysis of the inventory of the information campaign materials, it was concluded that the COMELEC failed to achieve its primary goals which was to educate the Filipino voters and to turn this knowledge into vote. Each stage of information campaign process was analyzed. The different elements of the information campaign were also examined to arrive at the conclusion. Factors that led to the outcome of the campaign were also determined. Implications of the result of the campaign are also included in this study. Such implications include the failure to democratize the Philippine electoral system by means of equal representation and the inability of the COMELEC to carry out such a massive information campaign. Several recommendations for future information campaigns as well as for future studies were then given. These include the consideration of the appropriate communications media to use for the campaign as well as the use of Filipino as a medium of discourse. It is also recommended for the campaign planners to plan and implement ahead of time and for the government to allocate enough budget for campaign of such nature.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Campaign management -- Philippines; Campaign paraphernalia -- Philippines